Some Aspects of Insect Behaviour under Field Conditions. I. Hatching and Migration of Caterpillars of Chilo zonellus Swinhoe (Lepidoptera: Pyralidae). - Katiyar, R. N. (Contributions to Entomology = Beiträge zur Entomologie, 1962)
Chilozonellus Swinhoe is one of the serious pests of maize (Zea mays), jowar (Sorghum vulgare) and sugarcane (Saccharum officinarum) in India. The hatching and migration of the pest during its developmental period has been studied to help in evolving the more effective means of its control. The eggs of Chilo hatch in the morning hours of the day. The extent of migration of caterpillars of early instars from the egg masses oviposited on the central shoot is very limited in the beginning due to the quicker availability of the food and more marked when the larvae are grown up, whereas the caterpillars of early instars from the egg masses on the lower leaves disperse immediately after hatching and later on the migration is comparatively slowed down. At the young stage of the crop all the parts of a plant are relished by the caterpillars, but when the crop is grown up the attack of Chilo is limited to the buds situated at each node. As the leaf sheaths covering these buds are also grown up and fibrous, the caterpillars do not like to cut the leaf sheath and reach the bud to eat, but they crawl under the leaf sheaths and then bore through the buds. The relation of the study of these habits with the possibility of breeding a resistant variety against Chilo has also been discussed.